2020
DOI: 10.4314/mmj.v32i3.2
|View full text |Cite
|
Sign up to set email alerts
|

The Malawi Orthopaedic Association/AO Alliance guidelines and standards for open fracture management in Malawi: a national consensus statement

Abstract: BackgroundOpen fractures are common injuries in Malawi that pose a large burden on the healthcare system and result in long-term disability.AimEstablishing a multiprofessional agreement on the management of open fractures in Malawi from a consensus meeting. MethodsAO Alliance convened a consensus meeting to build an agreement on the management of open fractures in Malawi. Eighteen members from different professions and various regions of Malawi participated in a 1-day consensus meeting on 7 September 2019. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…In HICs, the creation of major trauma networks has aided fracture care management [ 24 , 25 ] and there is potential to develop a trauma network system in Malawi and similar LMICs along similar lines. The introduction of guidelines has strengthened open fracture care in the UK [ 25 ] and a recent initiative has established locally approved guidelines for the care and referral of open fractures in Malawi [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In HICs, the creation of major trauma networks has aided fracture care management [ 24 , 25 ] and there is potential to develop a trauma network system in Malawi and similar LMICs along similar lines. The introduction of guidelines has strengthened open fracture care in the UK [ 25 ] and a recent initiative has established locally approved guidelines for the care and referral of open fractures in Malawi [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, both prompt administration of antibiotics and documented examination of neurovascular status are key features of the Malawi Orthopaedic Association (MOA) guidelines for management of open fracture [37]. Few participants gave antibiotics, or checked for distal neurological or vascular compromise, which are potentially simple examination techniques to identify need for urgent intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Compliance with the Malawi Orthopaedic Association/ Arbeitsgemeinschaft fur Osteosynthesefragen Alliance open fracture guidelines 26 …”
Section: Protocolmentioning
confidence: 99%
“…Some studies have shown that adherence to national guidance can reduce healthcare utilisation for severe open tibia fractures in the UK 24 , 25 . Recently, open fractures guidelines have been developed in Malawi via a consensus meeting 26 as resources such as computed tomography and specialised orthoplastic theatre lists are often not available in Malawi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation